АНАЛІЗ ПЕРЕДУМОВ ПОШКОДЖЕННЯ ЕЛЕГАЗОВИХ ВИМИКАЧІВ У ЕЛЕКТРИЧНИХ МЕРЕЖАХ 750 кВ - Кузнецов, В.Г.; Тугай, Ю.І.; Шполянський, О.Г. (Інститут електродинаміки Національної академії наук України, 2017)
To improve performance reliability of SF6 circuit breakers, an analysis of the possible reasons for their failure, which cannot be detected by traditional monitoring, was performed. As an example, a development of the situation, which led to SF6 circuit breaker damage at "Pivnichnoukrainska" 750kV-substation, was considered. Based on the records received from "REGINA" recorder, the analysis of operating parameters preceding the damage was performed. Matlab/Simulink environment was used to develop a digital model and simulate switching transient phenomena in 750kV transmission lines of "Pivnichnoukrainska-Kurska APS". Potentially hazardous operating conditions for SF6 circuit breakers were identified and recommendations for their prevention were given.  References 5, figures 5, tables 4.